Musculoskeletal desmoid tumours: Pre‐ and post‐treatment radiological appearances. Issue 4 (10th June 2015) - Liu, Daniel; Perera, Warren; Schlicht, Stephen; Choong, Peter; Slavin, John; Pianta, Marcus
Summary: This study was aimed to illustrate the pre‐ and post‐treatment imaging findings of musculoskeletal desmoid tumours and describe current treatment methods. Imaging of histologically proven cases of desmoid tumours at St. Vincent's Hospital, Melbourne, were obtained via picture archiving communication system (PACS) and then assessed by two musculoskeletal radiologists. Suitable imaging both pre‐ and post‐treatment were then obtained from PACS. All imaging chosen were de‐identified. Ninety‐two patients were found to have histologically proven cases of desmoid tumours between January 2000 and December 2013. Six patients with extra‐abdominal tumours were selected, where pre‐ and post‐treatment imaging was available. Desmoid tumours can occur in many areas of the body. Treatment of desmoids are varied. Although wide‐margin surgery has been the traditional form of treatment, it still cannot guarantee absence of tumour recurrence despite microscopically tumour‐free margins. Other forms of treatment such as non‐steroidal anti‐inflammatory drugs, radiotherapy, chemotherapy, tyrosine kinase inhibitors and also the conservative 'watch and wait' approach have been suggested, which show varying results.